Integrated circuits for channel coding in 3G cellular mobile wireless systems. - Thomas, C. (IEEE Communications magazine)
Error control coding is a key element of any digital wireless communication system, minimizing the effects of noise and interference on the transmitted signal at the physical layer. In 3G mobile cellular wireless systems, error control coding must accommodate both voice and data users, whose requirements vary considerably in terms of latency, throughput, and the impact of errors on the user application. At the base station, dedicated hardware or readily reconfigurable components are needed to address the concurrent coding and decoding demands of a large number of users with different call parameters. In contrast, the encoder and decoder at the user equipment (UE) are dedicated to a single call setup which changes infrequently. In designing encoder and decoder solutions for 3G wireless systems, not only are the performance issues important, but also the costs. Cellular wireless infrastructure manufacturers need to reduce costs, maximize system reuse, and increase flexibility in order to compete in the market. Furthermore, future-proofing a network is a primary concern due to the high cost of deployment. For the UE, power consumption (battery life) and size are key constraints in addition to manufacturing costs. This article considers the 3G decoder design problem and, using case studies, describes two 3G decoder solutions using ASICs. The first device is targeted for base station deployment and is based on a unified architecture for convolutional and turbo decoding. The second device is a dedicated high-speed radix-4 logMAP turbo decoder targeted for UE, motivated by the requirements for high-speed downlink packet access. Both devices have been fabricated in 0.18 μm CMOS technology, and while optimized for either base station or UE, may be used in both applications.